Active biodegradable films based on thermoplastic starch and poly (ε-caprolactone):technological application of antioxidant extracts from rice husk (2020)
Films of a polymeric material based on cassava starch and polyε-caprolactone (PCL) with antioxidant properties were made.The influence of PCL and the antioxidant extract were evaluated, over the mechanical, thermal and chemical properties of thefilms. They were elaborated with, and without the antioxidant extract, which is rich in polyphenolic compounds. The films wereconditioned at 20°C and 53% RH. The antioxidant extract was obtained from rice husk, by the hot water methodology in ahigh-pressure reactor, at 160°C and 10 bar. The total phenolic content of the extract was 12.27 (mEAG/100g dry matter), and theantioxidant activity had a value of 6691.95 (mETRX/100g dry matter). The extract was incorporated into a thermoplastic starchand poly E-caprolactone matrix, and films by compression molding were obtained. The antioxidant capacity was evaluatedby DPPH method, where the lesser value was 1.54 (kg film/g DPPH) from EC50, it was found that the addition of PCL andantioxidant improved the general properties of the films.